Discrepancies between ePrescriptions and dispensing in Belgium, 6 years after the launch of the electronic prescribing – a mixed-method study. Issue 2 (4th March 2022) - Van Laere, S.; Tommelein, E.; Dreesen, E.; Buyl, R.; Cornu, P.
ABSTRACT: Objectives: The number of electronic prescriptions (ePrescriptions) grows steadily in Belgium as in other European countries. In the future, Belgium wants to dematerialize the ePrescription flow, removing all paper trails. A quality check of the digital content and implementation of national ePrescription guidelines in the field was conducted, comparing the content at both prescription and pharmacy side. Methods: An explanatory mixed-methods design was applied. In a first phase, potential problems (warning flags) were identified by consulting stakeholders. Secondly, the warning flags were validated to problems (errors) in a random set of ePrescriptions collected in April 2019. In a third phase, explanatory interviews were held with various stakeholders in order to find explanations and to identify the initiators of these errors. Results: In the first phase, 15 warning flags were identified to evaluate the quality of an ePrescription. In the second phase, a random selection of 11, 798 ePrescriptions was validated. The most prevalent errors found, were the digital construction of the messages (18.88%), combined with lots of necessarily deemed substitutions by the pharmacist (3.39%) not following what was prescribed originally. In the third phase, stakeholders indicated that software of the prescriber and the use of inconsistent databases between prescriber and pharmacy can often be seen as the cause and initiator of these problems. Conclusions: Use of authentic medication databases and well-designed software systems have the potential to solve ePrescription problems. Focus should go to prevention instead of detection.